2018
DOI: 10.1136/bmjopen-2017-019267
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in patients in home healthcare: a retrospective record review using trigger tool methodology

Abstract: ObjectiveHome healthcare is an increasingly common part of healthcare. The patients are often aged, frail and have multiple diseases, and multiple caregivers are involved in their treatment. This study explores the origin, incidence, types and preventability of adverse events (AEs) that occur in patients receiving home healthcare.DesignA study using retrospective record review and trigger tool methodology.Setting and methodsTen teams with experience of home healthcare from nine regions across Sweden reviewed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 23 publications
1
70
0
6
Order By: Relevance
“…The IHI Global Trigger Tool [18] has been used since 2008. Trigger tools have also been adapted for specific areas, such as paediatric care [19,20], primary care [21] and home healthcare [22]. In mental health services there is a trigger tool for measuring adverse drug events [23], and a combined trigger tool for detecting somatic AEs and mental health-related patient safety incidents [12].…”
Section: Introductionmentioning
confidence: 99%
“…The IHI Global Trigger Tool [18] has been used since 2008. Trigger tools have also been adapted for specific areas, such as paediatric care [19,20], primary care [21] and home healthcare [22]. In mental health services there is a trigger tool for measuring adverse drug events [23], and a combined trigger tool for detecting somatic AEs and mental health-related patient safety incidents [12].…”
Section: Introductionmentioning
confidence: 99%
“…The provision of healthcare services is primarily the responsibility of the 21 county councils in Sweden. There are also 290 Swedish municipalities that have a legal obligation to take a recent retrospective record review in home care settings in Sweden (Schildmeijer et al, 2018), AEs were identified in 37.7% of the records examined, with 71.6% of AEs considered preventable. The most common AEs found were healthcare-associated infections, falls, and pressure ulcers.…”
Section: Settingmentioning
confidence: 99%
“…The GTT was initially developed to monitor AE rates over time and measure the effectiveness of patient-safety interventions 118,119 . The GTT has been used internationally for retrospective reviews in patient safety initiatives, initially within hospital care [120][121][122] , but it is now spreading to other healthcare settings 123,124 .…”
Section: Global Trigger Tool (Gtt)mentioning
confidence: 99%